Distortion in music production : the soul of sonics - Bromham, Gary; Moore, Austin (Music producer) (New York : Focal Press, 2023)
Distortion in Music Production offers a range of valuable perspectives on how engineers and producers use distortion and colouration as production tools. Readers are provided with detailed and informed considerations on the use of non-linear signal processing, by authors working in a wide array of academic, creative, and professional contexts. Including comprehensive coverage of the process, as well as historical perspectives and future innovations, this book features interviews and contributions from academics and industry practitioners. Distortion in Music Production also explores ways in which music producers can implement the process in their work and how the effect can be used and abused through examination from technical, practical, and musicological perspectives. This text is one of the first to offer an extensive investigation of distortion in music production and constitutes essential reading for students and practitioners working in music production.
Keywords: Sound recordings -- Production and direction; Electric distortion; MUSIC / General; TECHNOLOGY / Acoustics & Sound